2009
DOI: 10.4261/1305-3825.dir.2895-09.2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the maxillary bone in adults with nasal polyposis: a CT morphometric study

Abstract: Chronic nasal obstruction is a common complaint in otorhinolaryngology outpatient practice (1, 2). Causes of nasal obstruction, conditioning mouth breathing, include nasoseptal deviation, hypertrophied lower turbinates, adenoids and tonsils, chronic or especially allergic rhinitis, nasal trauma, congenital nasal deformities, foreign bodies, nasal polyps, and tumors (3). One of the most common causes of nasal obstruction in adults is nasal polyposis (NP) (1, 2). Computed tomography (CT) is the ideal imaging met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…In the study on patients with NP and healthy subjects, Serter et al [2] found that there was an increase in IAD and decrease in palatal bone depth in NP similar to our findings. In addition to these findings, we found that IAD was decreased; palatal bone depth was increased and these values were more prominent in patients with CS than those with SD.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the study on patients with NP and healthy subjects, Serter et al [2] found that there was an increase in IAD and decrease in palatal bone depth in NP similar to our findings. In addition to these findings, we found that IAD was decreased; palatal bone depth was increased and these values were more prominent in patients with CS than those with SD.…”
Section: Discussionsupporting
confidence: 81%
“…There is an increased interalveolar distance (IAD) as a result of enlarged maxillary bone due to expansion of nasal cavity caused by polyps. This causes flatting of palatal curve [2]. On the other hand, dome-like palatal bone curve and decreased IAD develop in patients with septum deviation due to mouth breathing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding anatomical variability of organs, structures and their parts at all the stages of human development is rather topical [2]. Defects of the dentoalveolar system rank one of the main places among pathology of the maxillary-facial region, and according to the data of certain authors their occurrence is from 70 to 80% [1,3,4,16]. One of the common congenital developmental defects of the maxillaryfacial region is cleft of the lip and hard palate named "harelip" and "cleft palate".…”
Section: Introductionmentioning
confidence: 99%